2010
DOI: 10.1111/j.1349-7006.2010.01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐II trial of combination treatment of interferon‐α, cimetidine, cyclooxygenase‐2 inhibitor and renin‐angiotensin‐system inhibitor (I‐CCA therapy) for advanced renal cell carcinoma

Abstract: We have recently reported favorable responses to a combination treatment comprising cimetidine, a cyclooxygenase-2 inhibitor and a renin-angiotensin-system inhibitor in metastatic renal cell carcinoma (RCC). In view of the potential synergistic effects of these three agents and interferon-a (I-CCA therapy), we conducted a phase-II trial to examine the efficacy and toxicity of I-CCA as firstline treatment. Fifty-one patients with advanced RCC received natural interferon-a (3-6 million U thrice/week) and cimetid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Nakai et al (2010) reported that the use of angiotensin-converting enzyme inhibitors or ARBs with gemcitabine was an independent prognostic factor for both progression-free survival and overall survival in patients with advanced pancreatic cancer. Two prospective studies also proposed the potency of AT1R blockade in cancer treatment (Yoshiji et al , 2009; Tatokoro et al , 2011). Although an increasing body of evidence suggests the efficacy of ARBs may be promising, we examined the effect of combination therapy consisting of CDDP and olmesartan in T24PR tumours, and found no significant difference in tumour growth between the ARB-only group and CDDP+ARB-treated group (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Nakai et al (2010) reported that the use of angiotensin-converting enzyme inhibitors or ARBs with gemcitabine was an independent prognostic factor for both progression-free survival and overall survival in patients with advanced pancreatic cancer. Two prospective studies also proposed the potency of AT1R blockade in cancer treatment (Yoshiji et al , 2009; Tatokoro et al , 2011). Although an increasing body of evidence suggests the efficacy of ARBs may be promising, we examined the effect of combination therapy consisting of CDDP and olmesartan in T24PR tumours, and found no significant difference in tumour growth between the ARB-only group and CDDP+ARB-treated group (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, with respect to cancer treatment, a few reports evaluated the efficacy of RAS inhibitor administration, and most reported positive outcomes, especially in combination with other anti-cancer agents (Uemura et al , 2005; Wilop et al , 2009; Nakai et al , 2010; Tatokoro et al , 2011). Wilop et al analysed retrospectively 287 patients with advanced non-small cell lung cancer undergoing first-line platinum-based chemotherapy, and reported that patients receiving either ACEIs or ARBs had a median survival that was 3.1 months longer than non-recipients (11.7 vs 8.6 months) (Wilop et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent investigations have revealed that external symptoms of systemic inflammation are significant predictors of poor outcome in many cancers. [10][11][12][13] To obtain a better understanding of the underlying mechanism of inflammation as it relates to cancer progression, some therapeutic approaches that target the cancer-associated inflammation have been shown to be effective, such as cyclooxygenase-2 inhibitor in combination with IFN-a for RCC, 14,15 and aspirin for colorectal cancer. 16 Quantification of the systemic inflammatory response is essential to adequately evaluate the activity or outcomes of inflammation-related diseases.…”
Section: Systemic Inflammation and Crp In Cancermentioning
confidence: 99%